2010
DOI: 10.1007/s11524-009-9394-z
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Inequalities in Induced Abortion According to Educational Level among Urban Women

Abstract: This study aims to describe trends in inequalities by women's socioeconomic position and age in induced abortion in Barcelona (Spain) over 1992-1996 and 2000-2004. Induced abortions occurring in residents in Barcelona aged 20 and 44 years in the study period are included. Variables are age, educational level, and time periods. Induced abortion rates per 1,000 women and absolute differences for educational level, age, and time period are calculated. Poisson regression models are fitted to obtain the relative ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Consistent with previous studies, we found an association between birthplace and IAs [19, 3537] underscoring the importance of educational attainment on having IAs [20, 22, 28, 38]. Similarly, previous studies have examined the effect of birthplace and education on repeat IAs [21, 24, 27, 39].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous studies, we found an association between birthplace and IAs [19, 3537] underscoring the importance of educational attainment on having IAs [20, 22, 28, 38]. Similarly, previous studies have examined the effect of birthplace and education on repeat IAs [21, 24, 27, 39].…”
Section: Discussionsupporting
confidence: 91%
“…Induced abortion (IA), an indicator of reproductive health, has been associated with both to birthplace [1924] and educational attainment [2528]. Studies examining IA and birthplace suggest that compared to natives women, immigrant women exhibited higher IA rates, number of repeated and IAs performed during the second trimester of pregnancy [2124].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand are those studies which have focused on individual determinants which may influence, to a greater or lesser degree, why women have abortions, such as women’s employment status (Delgado and Barrios, 2007; Rasch et al, 2002), educational level (Font-Ribera et al, 2008; Pérez et al, 2010), civil status and age (Delgado and Barrios, 2007; Galobardes et al, 2006; Llorente-Marrón et al, 2016; Väisänen, 2017) and immigrant status (Helstrom et al, 2003; Pérez et al, 2013), among others.…”
Section: Research On Induced Abortionmentioning
confidence: 99%
“…, Pérez et al . , 2014, Zurriaga et al . ), there is a lack of empirical evidence in Spain on the complex interplay of social and personal dimensions contributing to the decision to have an abortion.…”
Section: Introductionmentioning
confidence: 99%